Pleomorphic liposarcoma: An analysis of 6 case reports and literature review. Issue 8 (February 2018) - Wang, Lianwei; Luo, Runlan; Xiong, Zuming; Xu, Jinming; Fang, Dengyang
Abstract: Rationale: Pleomorphic liposarcoma (PLS), is a rare subtype of liposarcoma, and is considered to be of the highest malignancy grade. Patient concerns: We aimed to analyze the clinical features, diagnosis, treatment, and recurrence of the 6 cases of PLS. Diagnoses: Six cases with confirmed pathological PLS presented at out hospital from January 2003 to January 2017. The postoperative pathology of 5 cases confirmed PLS, and the other was confirmed as PLS with well-differentiated liposarcoma. Interventions: All 6 patients underwent complete tumor resection at the time of the first definite diagnosis, and one of them had underwent 3 cycles of chemotherapy treatment. Outcomes: There were 4 cases with local recurrence and surgery was repeated after the first radical excision. One case was not recurrent after 27 months post-operation, and the other was lost. The shortest recurrence time of all of these cases was 4 months, and the longest was 29 months after the first radical surgery. Lessons: PLS is a rare and high-grade malignancy with high recurrence, poor prognosis, and its treatment is still highly controversial. More studies are required to determine the appropriate treatment and therapeutic strategies to improve the survival rate of patients with PLS, as the disease is associated with frequent relapse.